Situation report on Nepal’s agrifood systems: August 2024 - Palikhe, A.; Maharjan, N.K.; Adhikari, Madan; Gupta, S.; Kumar, Anjani; Minot, Nicholas; Koirala, P.; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2024)
The year-on-year annual Consumer Price Index (CPI) reached its lowest for 2023/24 at 3.6 but the CPI for food and beverage was higher than the national CPI indicating higher costs for these essential items compared to other non-goods and services. Annual remittance inflow increased by 16.5 percent in July 2024, although the increase was lower than the same period of the previous year. The number of Nepali workers applying for entry renewal declined by 1.4 percent.